Dengue Virus Capsid Protein Dynamics Reveals Spatially Heterogeneous Motion in Live-Infected-Cells - Gabriel, Manuela (2020)
Dengue is the single most important human viral infection transmitted by insects. The function of the viral proteins andtheir interactions with the host cell is under exhaustive investigation with the aim of identifying antiviral strategies. Here,using recombinant full-length dengue virus genomes, carrying a fluorescent mCherry fused to capsid, we studied biophysicalproperties of the viral protein during one infectious cycle in living cells. Dengue virus capsid protein associates to differentcellular compartments but its function in these locations is largely unknown. We evaluated the diffusion of capsid inside the celland determined a higher effective diffusion coefficient in the cytoplasm than in the nucleus. Using advanced fluorescencecorrelation methods, including the recently developed two-dimensional pair correlation analysis, we constructed for the first timehigh resolution maps of capsid mobility in an infected cell. We observed that the motion of capsid in the nucleoplasm-nucleolusinterface was highly organized, indicating an obstacle in this interface. Although nucleoli are membraneless structures, theydisplayed liquid-liquid phase separation. Once inside nucleoli, the protein showed isotropic mobility, indicating free diffusion orimmobilized capsid inside these structures. This is the first study presenting spatial and temporal dynamics of the dengue viruscapsid protein during infection.